Using food intake records to estimate compliance with the Eatwell Plate dietary guidelines. Issue 2 (13th August 2015) - Whybrow, S.; Macdiarmid, J. I.; Craig, L. C. A.; Clark, H.; McNeill, G.
Abstract: Background: The UK Eatwell Plate is consumer based advice recommending the proportions of five food groups for a balanced diet: starchy foods, fruit and vegetables, dairy foods, nondairy sources of protein and foods and drinks high in fat or sugar. Many foods comprise ingredients from several food groups and consumers need to consider how these fit with the proportions of the Eatwell Plate. This involves disaggregating composite dishes into proportions of individual food components. The present study aimed to match the diets of adults in Scotland to the Eatwell Plate dietary recommendations and to describe the assumptions and methodological issues associated with estimating Eatwell Plate proportions from dietary records. Methods: Foods from weighed intake records of 161 females and 151 males were assigned to a single Eatwell group based on the main ingredient for composite foods, and the overall Eatwell Plate proportions of each subject's diet were calculated. Food group proportions were then recalculated after disaggregating composite foods. Results: The fruit and vegetables and starchy food groups consumed were significantly lower than recommended in the Eatwell Plate, whereas the proportions of the protein and foods high in fat or sugar were significantly higher. Failing to disaggregate composite foods gave an inaccurate estimate of the food group composition of the diet. Conclusions: Estimating Eatwell Plate proportions from dietary records is not straightforward, and is reliant on methodological assumptions. These need to be standardised and disseminated to ensure consistent analysis.